The Role of ESG (Environmental, Social, and Governance) Investment in Attracting Global Investors - Rina Haji Omar; Ilham Ilham (Journal of Multidisciplinary Sustainability Asean, 2025)
Background. Environmental, Social, and Governance (ESG)-based investments are increasingly becoming a major concern in global investment decisions. Investors are starting to consider sustainability factors as an important aspect in assessing the risks and opportunities of a company. Changes in regulations and increased awareness of environmental and social issues have prompted companies to adopt ESG standards to increase their investment attractiveness. Purpose. The study aims to analyze the extent to which ESG influences global investor decisions and how certain ESG factors contribute to increased investor confidence. The main focus of the research is to identify the most significant ESG elements in attracting investment as well as measuring their impact on a company's access to funding. Method. The research method uses a quantitative approach with regression analysis of ESG data from 50 global companies. Data sources are obtained from financial and ESG statements published by companies as well as secondary data from ESG rating agencies. The analysis was conducted to identify the relationship between the ESG score and the amount of investment a company obtained. Results. The results of the study show that companies with high ESG scores get greater investment than companies with low ESG scores. ESG report transparency and compliance with sustainability regulations are key elements in increasing investor confidence. The renewable energy and green technology sectors are the sectors that benefit the most from this trend. Conclusion. The conclusion of this study confirms that ESG is not just a sustainability strategy, but has become a key factor in global investment attractiveness. Companies looking to improve access to funding need to strengthen their ESG policies by increasing transparency and compliance with sustainability regulations.